2007
DOI: 10.1002/cjoc.200790005
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Ethylene Oligomerization Catalytic Activity of {2‐Carbethoxy‐6‐[1‐[(2,6‐diethyl‐phenyl)imino]ethyl]pyridine}CoCl2

Abstract: The unsymmetric precursor ethyl 6-acetylpyridine-2-carboxylate (4) was synthesized from 2,6-dimethylpyridine (1). On the basis of this precursor, a new mono(imino)pyridine ligand (5) and the corresponding Co(II) complex {2-carbethoxy-6-[1-[(2,6-diethylphenyl)imino]ethyl]pyridine}CoCl 2 (6) were prepared. The crystal structure of complex indicates that the 2-carbethoxy-6-iminopyridine is coordinated to the cobalt as a tridentate ligand using [N, N, O] atoms, and the coordination geometry of the central cobalt i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Although a number of mono(imino)pyrrole ligands were developed, nearly all of the reported ligands bore H side arms [10][11][12][13][14][15][16]. We have expanded this work to mono(imino) pyrrole ligands with a -CH 3 side arm in order to have greater electronic and steric effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a number of mono(imino)pyrrole ligands were developed, nearly all of the reported ligands bore H side arms [10][11][12][13][14][15][16]. We have expanded this work to mono(imino) pyrrole ligands with a -CH 3 side arm in order to have greater electronic and steric effects.…”
Section: Introductionmentioning
confidence: 99%
“…Bis(imino)pyridyl-metal catalysts have been an attractive research field because of their flexible structural modifications and complexation between ligand and metal, as well as outstanding catalytic performance. Studies have mainly concentrated on adjusting the structure of the ligand, usually using the following ways [5][6][7][8]: (1) introducing heteroatoms to the pyridine ring to get an N-based sixmembered heterocyclic imino ligand, such as pyrimidine, pyrazine, and triazine ligands; (2) replacing the six-membered heterocycle with a five-membered heterocycle such as a pyrrole, thiophene, or furan ring; (3) modifying the imino substituent to get ligands with different side arms, such as carbazole or Pybox ligands [9]; or (4) changing the symmetric bis (imino) structure to an asymmetric structure [10][11][12][13]. For example, zirconium and titanium complexes bearing mono(imino)pyrrole ligands, reported by Fujita [14,15] and Bochmann et al [7], were demonstrated to be good catalysts for ethylene polymerization.…”
Section: Introductionmentioning
confidence: 99%